Caracterização e análise da sustentabilidade da atividade pesqueira na República da Guiné-Bissau, costa ocidental da África - Teixeira, Sebastião Ribeiro D'Alva (2022)
Fishing is a strategic sector regarding to the general development efforts of the Republic of Guinea-Bissau, a country in West Africa. It has been responsible for one of the largest tax and foreign exchange earnings of the country’s economy, in addition to being an important sector of the national strategy in the fight against poverty and in favor of food security. The objective of the present work consisted of the characterization and analysis of the sustainability of the fishing activity in Guinea-Bissau. Primary data, collected in the Port of Alto Bandim, were used for characterization of the fishing activity, and secondary data, obtained from the Center for Applied Fisheries Investigation (CIPA), of the Ministry of Fisheries of Guinea-Bissau. Secondary data were used to analyze industrial fishing production in 2019. Seventy-five semi-structured questionnaires were applied to artisanal fishermen in Bissau, from May to July 2021, for the analysis of the sustainability of artisanal fisheries, using the artisanal fisheries sustainability index (). The average monthly fish production was 11,709.28 ± 5,177.74 tons in 2019, with sardinella, horse mackerel, mackerel and catfish, being the main species caught. The trawling modality of pelagic fish was the one that most contributed to the total national production with 42.63%. The captured marine ichthyofauna was composed of 16 orders, 40 families and 65 species. Ecological indices, considering rainy and dry seasons, showed the highest values for the rainy season, with Shannon-Wiener diversity index (H′) equal to 2.47, Pielou evenness (E) equal to 0.58, and the Margalef species richness index (d) equal to 3.79. The demersal species presented H′, E and d of 2.98, 0.78 and 2.56, respectively, higher than those found for the pelagic species. The total fisheries yield (IR) in 2019 was 9,848.01 kg/day or 339.03 kg/lance. The highest IR values were obtained in the trawling of pelagic fish, with 42,876.46 kg/day or 3,031.30 kg/cast, and in the trawling of cephalopods, with 14,506.99 kg/day or 408.63 kg /throw. The artisanal fisheries sustainability index (ISPA) of the Autonomous Sector of Bissau was 0.677, indicating a medium or intermediate level of sustainability. All the information presented in this work is of great importance to ensure the sustainable exploitation of fisheries, and should be taken into account in the establishment of public policies that promote its management.